Foreign-held U.S. government securities and monetary policy in United States - Lucia, J.L. (Economic & Social Studies, 1974)
The American deficit in the balance of payments of recent years has had its counterpart in the accumulation of US government securities in the hands of foreigners. Dollars earned by foreigners have been, to a large extent, invested in US government securities. In 1966, foreign official institutions, mainly foreign central banks, held 6.316 billion dollars in US Treasury bills; by May of 1973 this total had risen to 35.736 billion. Marketable US government securities (held mainly by foreign central banks) rose in the same period from 2.329 billion to more than 7 billion dollars; non-marketable government securities (bonds and notes) increased from 695 million in 1966 to 16.012 billion in May of 1973.
Keywords: Balance of payments - United States; National deficit - United States